Structure, ferroelectric and piezoelectric properties of multiferroic Bi0.875Sm0.125FeO3 ceramics - Chen, Xiaomin (2013)
With a rhombohedra-like structure, the Bi0.875Sm0.125FeO3 ceramics show much-improved ferroelectric and piezoelectric properties: a saturated ferroelectric polarization of 40 μC/cm2 and a piezoelectric d33 of 45 pC/N at 20 °C. After the polarized sample was annealed at 600 °C, its d33 decreases to ∼20 pC/N. Besides, Bi0.875Sm0.125FeO3 shows dielectric or impedance resonances at 20–550 °C, suggesting that the ferroelectric component with high Curie temperature still partially remained at 550 °C. However, the impedance and the resistance decrease so fast with temperature increasing that both of them are below 1000 ohm above 420 °C. Even so, this piezoelectric resonance method can explore leaky ferroelectrics at high temperature.